Análisis del sistema turístico de la parroquia Casacay,Pasaje,Ecuador - Pineda Reasco, Ariana Paulett; Sojos Lopez, Genesis Lisbeth (My University, 2020)
The tourist management of the Pasaje canton seeks to strengthen the tourist attractions available to it nationally. Among those that stand out freshwater spas, adventure tourism practice and areas with optimal biodiversity to promote tourism. The tourist activity in the rural areas allows to increase the economy and the development of projects focused on tourism in search of the sustainable use of natural and cultural resources. Through the analysis of the tourism system which includes the result of a series of interrelated factors (internal and external). The main objective of the research is to identify the current state of the Casacay parish, and the indicators that can boost tourism activity in the territory. The methodology used was the descriptive exploratory method through the survey and ranking of tourist attractions of MINTUR with a direct observation approach. The results reflected that there are potential natural resources to carry out recreation activities, in addition to statistical data of the indicators for the benefit of the community for the management and development of strategies.
La gestión turística del cantón Pasaje busca potenciar a nivel nacional los atractivos turísticos que dispone.Entre los que destacan balnearios de agua dulce, práctica de turismo de aventura y zonas con biodiversidad óptimos para promover el turismo. La actividad turística en las zonas rurales permite incrementar la economía y el desarrollo de proyectos enfocados al turismo en busca del aprovechamiento sostenible de los recursos naturales y culturales, a través del análisis del sistema turístico, el cual comprende el resultado de una serie de factores interrelacionados (internos y externos). El objetivo principal de la investigación es identificar el estado actual de la parroquia Casacay, y los indicadores que pueden potenciar la actividad turística en el territorio. La metodología empleada fue el método exploratorio descriptivo mediante la ficha de levantamiento y jerarquización de atractivos turísticos del MINTUR con un enfoque de observación directa. Los resultados plasmaron que existe recursos naturales potenciales para realizar actividades de recreación, además de datos estadísticos de los indicadores en beneficio de la comunidad para la gestión y desarrollo de estrategias.
Keywords: SISTEMA TURÍSTICO; POTENCIALIDAD; RECURSOS TURÍSTICOS; FACTORES INTERNOS Y EXTERNOS